2022
DOI: 10.1051/shsconf/202213501002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Students’ Intentions to Create Green Start-ups: A Theory of Planned Behaviour Approach

Abstract: Start-ups play a fundamental role in the economy and have contributed enormously and effectively to solving economic and social issues. However, despite the significant environmental hazards the world is experiencing, the environmental dimension of its contribution is still significantly low, and the transition to green start-ups is still in its infancy especially in developing countries. The aim of the paper is to identify the factors that influence students’ intentions to create green start-ups. Based on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 27 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…Hence, it is logical for volunteers to gravitate away from the traditional form to the new form of volunteering. Our results support the findings of a study carried out by Bouarar et al (2021), which revealed that "fear of COVID-19" was the strongest antecedent of intention. Lachance (2020) noted that perceived COVID-19 threats limited traditional volunteer activity, while revealing that COVID-19 created great opportunities for digital volunteering.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, it is logical for volunteers to gravitate away from the traditional form to the new form of volunteering. Our results support the findings of a study carried out by Bouarar et al (2021), which revealed that "fear of COVID-19" was the strongest antecedent of intention. Lachance (2020) noted that perceived COVID-19 threats limited traditional volunteer activity, while revealing that COVID-19 created great opportunities for digital volunteering.…”
Section: Discussionsupporting
confidence: 91%
“…Great number of scholars have made use of TPB theoretical underpinning in their investigations of pro environmental behavior. Some of these studies integrated previous research or expanded on the paradigm offered by TPB (Bouarar, Mouloudj, Makhlouf & Mouloudj, 2022;Romero & Rodríguez, 2022). Despite the fact that TPB is generally helpful, number of research have attempted to enhance explanatory power of this theory by including other variables inside TPB model.…”
Section: Theory Of Planed Behavior and Ecopreneurship Intentionsmentioning
confidence: 99%
“…It is impossible to deny that TPB-based research has several theoretical benefits when applied to the field of entrepreneurship (Romero-Colmenares & Reyes-Rodríguez, 2022). TPB model has been used on number of occasions by several researchers on entrepreneurship for purpose of identifying entrepreneurial intents; nevertheless, its capacity to explain the desire to engage in sustainable entrepreneurship has not been thoroughly investigated (Bouarar et al, 2022). Many researches in this field have discovered the considerable beneficial influence of attitudes on entrepreneurial intentions.…”
Section: Theory Of Planed Behavior and Ecopreneurship Intentionsmentioning
confidence: 99%
“…We identified a few studies that extended TPB with variable pandemic-related fears towards OFS (Pal et al, 2022). Bouarar et al (2021) augmented TPB with trust and COVID-19 fear variables and observed that COVID-19 fear, together with subjective norms and attitudes, improves a user's inclination to use OFS. However, studies discussing consumers' protective motives with the use of OFS are not very elaborate and research in the field is still underway (Truong & Truong, 2022).…”
Section: Influence Of Tpb Variablesmentioning
confidence: 99%
“…Subjective norms define an individual's perceived social influence for getting or not getting involved in a certain behaviour or action (Bouarar et al, 2021). It explains the user's association with reference groups, which are used as a basis to refer to certain behaviour or perceptions.…”
Section: Pandemic Subjective Normsmentioning
confidence: 99%